Konsep Dasar Studi Perbandingan Pendidikan - Halimatul Fijriah; Mislaini Mislaini; Septia Yulia Ningsih (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Comparative studies of education are an approach used to compare various educational systems in different countries or cultures with the aim of understanding differences and similarities in educational practices.This research aims to explain the basic concepts of comparative education studies and the importance of this study in efforts to improve the quality of education globally.The data collection used by researchers is a literature study by studying and citing several sources from textbooks, articles, journals, modules and other publications. This comparative research is important to generate a better understanding of effective educational practices and to provide useful insights for educational reform in different countries.